Respuesta :

Answer:

[tex]\boxed{5 \cdot \sqrt{2} \cdot \sqrt[6]{5} }[/tex]

Step-by-step explanation:

[tex]\sqrt[3]{250} \cdot \sqrt{\sqrt[3]{10} }[/tex]

[tex]\sqrt{\sqrt[3]{10} } \implies (10^\frac{1}{3} )^\frac{1}{2} =10^\frac{1}{6} =\sqrt[6]{10}[/tex]

[tex]\therefore \sqrt{\sqrt[3]{10} }=\sqrt[6]{10}[/tex]

[tex]\text{Solving }\sqrt[3]{250} \cdot \sqrt{\sqrt[3]{10} }[/tex]

[tex]250=2 \cdot 5^3[/tex]

[tex]\sqrt[3]{250}=\sqrt[3]{2\cdot 5^3}=5 \sqrt[3]{2}[/tex]

Once

[tex]\sqrt[6]{2} \cdot \sqrt[6]{5} = \sqrt[6]{10}[/tex]

We have

[tex]5 \sqrt[3]{2} \cdot \sqrt[6]{2} \cdot \sqrt[6]{5}[/tex]

We can proceed considering the common base of exponentials

[tex]\sqrt[3]{2} \cdot \sqrt[6]{2} = 2^{\frac{1}{3}} \cdot 2^{\frac{1}{6} } = 2^{\frac{3}{6} } = 2^{\frac{1}{2} }=\sqrt{2}[/tex]

Therefore,

[tex]5 \sqrt[3]{2} \cdot \sqrt[6]{2} \cdot \sqrt[6]{5} = 5 \cdot \sqrt{2} \cdot \sqrt[6]{5}[/tex]